1974
DOI: 10.1177/000992287401301109
|View full text |Cite
|
Sign up to set email alerts
|

The Cotton-Tipped Swab

Abstract: Correspondence to Harvey Kravitz, M.D. 9243 Avers, Evanston, Ill. 60203. ! NJURY TO THE EARS and impaction of cerumen in the external auditory canals, with hearing loss caused by cotton-tipped swabs, has not received the attention it deserves in the literature. This report describes studies carried out to determine the frequency of such problems in children and adults. MethodsThe authors, who included three pediatricians and two otolaryngologists, collected data on ear diseases and disturbances related to cott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Sagiv et al [16] reported that the traumatic tympanic membrane perforations in pediatric patients tend to heal spontaneously than in adults. Clinical suspicion of ossicular dislocation, perilymphatic fistula that presents with symptoms of dizziness, vertigo, sudden or fluctuating sensorineural hearing loss, and facial nerve paralysis alerts physician for immediate otolaryngology consultation for surgical evaluation within hours to prevent permanent hearing loss [17].…”
Section: Management Of Pediatric Ear Traumamentioning
confidence: 99%
“…Sagiv et al [16] reported that the traumatic tympanic membrane perforations in pediatric patients tend to heal spontaneously than in adults. Clinical suspicion of ossicular dislocation, perilymphatic fistula that presents with symptoms of dizziness, vertigo, sudden or fluctuating sensorineural hearing loss, and facial nerve paralysis alerts physician for immediate otolaryngology consultation for surgical evaluation within hours to prevent permanent hearing loss [17].…”
Section: Management Of Pediatric Ear Traumamentioning
confidence: 99%